'Mirror, mirror on the wall, please tell me … ': the populist rhetoric of the 'new' media of 'new Turkey' during the April 16, 2017 referendum. (15th March 2021) - Erçetin, Tuğçe; Erdoğan, Emre
ABSTRACT: This article aims to explain how the media reproduced populist themes during the campaign for the constitutional referendum in 2017 by examining columns in pro-government newspapers and conducting a content analysis. The findings demonstrate that 'the people' were seen as the most significant opposition to the establishment. The 'us–them' distinction was mostly used, which was promoted by othering, emphasizing the moral superiority and victimization of the in-group and humiliating out-groups. The study argues that populist discourse is successful in making group differentiations and that pro-AKP elements in the media helped the government gain consent for its campaign for a 'new Turkey.'